Penguatan Peran Politik Ekonomi Sosial Budaya dalam Perlindungan Hukum Adat untuk Membangun Soliditas Masyarakat Dayak menghadapi Eksploitasi Sumberdaya Alam Kalimantan Barat - Sedia, Genopepa (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2024)
The Dayak nation views that so far the rhythm of development and culture has tended to be out of sync. Decentralization policy also contains the main paradigm to encourage the growth of democratization, public services, as well as higher participation and empowerment of regional communities. The real manifestation of the pro-community paradigm is shown by the change in the function of representative institutions and the mechanism for selecting Regional Heads from top-down to bottom-up, so that regional leaders are truly the result of the aspirations of local communities. Community Participation: The success of regional development in the era of autonomy is not in the hands of policy holders alone, but instead lies in the establishment of mutually reinforcing synergies (mutual interrelations) between the pillars of regional development, namely the regional government, the business world and the community. broadly including indigenous groups. Social system The social system of the Dayak community is closely related to the village. Each Village has a government led by a Village Head, Temenggung and/or Traditional Head and/or Supplier or Penghulu. The Village Head acts as the Administrative leader of the Village. Law Number 32 of 2009 concerning Environmental Protection and Management (UUPPLH) provides opportunities for the wider community in terms of monitoring and preparing spatial planning. As a legal instrument, UUPPLH seeks to strengthen environmental democracy. Strengthening democracy can be done through increasing access to information, public participation, access to justice and strengthening people's rights in environmental protection and management. The protection of Customary Law above at least shows that the role of women has the same dignity and status as men in terms of their role of mutual respect and respect in each other's lives. Recommendations from the national seminar on the X Gawai Dayak Week, Sintang Regency in 2023, were presented and read by the Drafting Team on the closing night of the X X Gawai Dayak Week, Sintang Regency, Monday evening, July 10 2023, to be followed up as appropriate by policy makers from the central level, the government Province to district government